Firms’ financial and real responses to credit supply shocks: Evidence from firm-bank relationships in Germany - Dwenger, Nadja; Fossen, Frank M.; Simmler, Martin (Journal of Financial Intermediation, 2020)
We investigate the importance of firm-bank relationships for the international transmission of bank distress to the real economy. Using a large panel of matched financial statements of firms of all sizes and their relationship banks in Germany, we find that banks with losses from proprietary trading activities during the 2007/8 financial crisis decreased their lending, and that their firm customers responded by reducing real investment and employment. We document how different types of firms partially offset reduced credit supply by resorting to alternative financing sources.